PEMBELAJARAN TEORI PROBABILITAS MENGGUNAKAN R - Joko Sungkono; Kriswianti Nugrahaningsih (Universitas Veteran Bangun Nusantara, 2020)
In learning probability theory, if a series of statistical experiments is carried out several times, identifying the possible samples produced is not an easy thing. If this happens, then a significant probability problem will arise. The objective of this study is how to learn probability theory using R software. Based on the simulation results it can be concluded that by combining the syntax in R can be used to solve probability problems such as identifying sample points from experiments, events, event operations, probabilities and conditional probabilities. This will help students learning in understanding of the probability theory material. The use of R will be very pronounced for experiments with a large enough scale that results in a large sample probability.